Strong-LAMP: A LAMP Assay for Strongyloides spp. Detection in Stool and Urine Samples. Towards the Diagnosis of Human Strongyloidiasis Starting from a Rodent Model. - Pedro Fernández-Soto; Alicia Sánchez-Hernández; Javier Gandasegui; Cristina Bajo Santos; Julio López-Abán; José María Saugar; Esperanza Rodríguez; Belén Vicente; Antonio Muro (Public Library of Science (PLoS), 2016)
BACKGROUND:Strongyloides stercoralis, the chief causative agent of human strongyloidiasis, is a nematode globally distributed but mainly endemic in tropical and subtropical regions. Chronic infection is often clinically asymptomatic but it can result in severe hyperinfection syndrome or disseminated strongyloidiasis in immunocompromised patients. There is a great diversity of techniques used in diagnosing the disease, but definitive diagnosis is accomplished by parasitological examination of stool samples for morphological identification of parasite. Until now, no molecular method has been tested in urine samples as an alternative to stool samples for diagnosing strongyloidiasis. This study aimed to evaluate the use of a new molecular LAMP assay in a well-established Wistar rat experimental infection model using both stool and, for the first time, urine samples. The LAMP assay was also clinically evaluated in patients´ stool samples. METHODOLOGY/PRINCIPAL FINDINGS:Stool and urine samples were obtained daily during a 28-day period from rats infected subcutaneously with different infective third-stage larvae doses of S. venezuelensis. The dynamics of parasite infection was determined by daily counting the number of eggs per gram of feces from day 1 to 28 post-infection. A set of primers for LAMP assay based on a DNA partial sequence in the 18S rRNA gene from S. venezuelensis was designed. The set up LAMP assay (namely, Strong-LAMP) allowed the sensitive detection of S. venezuelensis DNA in both stool and urine samples obtained from each infection group of rats and was also effective in S. stercoralis DNA amplification in patients´ stool samples with previously confirmed strongyloidiasis by parasitological and real-time PCR tests. CONCLUSIONS/SIGNIFICANCE:Our Strong-LAMP assay is an useful molecular tool in research of a strongyloidiasis experimental infection model in both stool and urine samples. After further validation, the Strong-LAMP could also be potentially applied for effective diagnosis of strongyloidiasis in a clinical setting.